Prevalence of Class Iii Malocclusion in Permanent Dentition - A Retrospective study - SHIVANNI, S.S.; S, ARVIND; R N, DR. BALAKRISHNA (The journal of contemporary issues in business and government, 2021)
The prevalence of malocclusion varies greatly among different race, ethnicity and geographic locations. Knowledge about the prevalence of malocclusion among the population helps in the early diagnosis and to provide a customized treatment plan for that population. The main aim of this study is to assess the prevalence of class III malocclusion in permanent dentition. The data were collected by analyzing the records of 86000 patients between June 2019-March 2020. The study includes 37756 patients above the age of 12 years in their permanent dentition who reported to the University in Chennai. The results were analysed and graphs were tabulated using SPSS software. Out of the total patients assessed, 365 patients (0.96%) had class III malocclusion among which 242 were males and 123 were females. It was further found that among the 365 patients, prevalence of class III malocclusion was 75.34% and class III subdivision was 24.66%. Chi square test done between type of malocclusion and gender was found to be insignificant with P value of 0.933. Within the limitations of the study, it was found that prevalence of class III malocclusion was less in our population with no significant difference in distribution among males and females.